2019
DOI: 10.6018/analesps.353761
|View full text |Cite
|
Sign up to set email alerts
|

Online sexual activities among university students: relationship with sexual satisfaction

Abstract: Título: Actividades sexuales online en estudiantes universitarios: relación con la satisfacción sexual. Resumen: Este estudio explora las actividades sexuales a través de internet y analiza la relación entre estas actividades y la satisfacción sexual. Un total de 236 estudiantes universitarios completaron los cuestionarios administrados. Los resultados indicaron que las actividades sexuales online más realizadas fue la búsqueda de temas sexuales, ligar a través de chats y consultar videos eróticos o pornográfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…at an increasingly young age (Ballester-Arnal et al, 2016). Additionally, we also found a high prevalence of online "sexual activities" among Spanish young adults (Gutiérrez-Puertas et al, 2020), as well as the use of social networks for flirting, searching for sexual information, purchasing sexual materials, etc., which is also significant and coincides with the international literature (Shaughnessy et al, 2013;Zheng & Zheng, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…at an increasingly young age (Ballester-Arnal et al, 2016). Additionally, we also found a high prevalence of online "sexual activities" among Spanish young adults (Gutiérrez-Puertas et al, 2020), as well as the use of social networks for flirting, searching for sexual information, purchasing sexual materials, etc., which is also significant and coincides with the international literature (Shaughnessy et al, 2013;Zheng & Zheng, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…In regards to adults, prior research has found that those who do not use pornography report the highest sexual satisfaction, particularly surrounding their satisfaction with their sexual partner and the amount of sexual activity they regularly engage in [41]. Although we reviewed evidence above suggesting that using pornography with a partner increases partnered sexual functioning, other research has shown that most pornography users typically consume pornography for the purposes of solitary masturbation, which is associated with decreased sexual satisfaction for both men and women [42][43][44][45][46].…”
Section: Pornography Use and Psychosocial Sexual Functioningmentioning
confidence: 99%
“…Out of the many types of OSAs, for the purpose of this study, two categories will be selected, solitary OSAs (e.g., watching pornography) and partnered OSAs (e.g., sex chat) [18]. Thus far, research concerning OSA has focused mainly on harmful outcomes, such as exposure trauma [19], positive attitudes towards uncommitted sex [20,21], risks for decreased social integration [22], abuse or addiction [23] and sexual dissatisfaction [24,25], reflecting interest in the new and uncertain threats related to the everexpanding digital domain. In contrast, very few studies have investigated less unpleasant outcomes of OSAs or, indeed, the relation between OSAs and the sexual self-concept.…”
Section: Introductionmentioning
confidence: 99%